The Role of Light Variation in the Attending to and Memorisation of Stained-Glass Windows: An Eye Tracking and Behavioural Study. - Nevin, Kate (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2024)
Stained-glass is a distinctive art form that both transmits and reflects light, making it a desirable medium for research on the effects of light on attention and memory. There have been few investigations exploring the impact of light variation when viewing stained-glass, despite a growing number of studies on the cognitive processes involved when perceiving art. This thesis investigates how visual attention is distributed when viewing stained-glass windows under various focal light conditions and how these differences in attention affect subsequent recognition memory for these stained-glass windows. We also explore how recognition memory for entire windows is affected by whether these windows are encoded under static or dynamic lighting conditions. In this thesis we show that light variation in stained-glass windows can make the features depicted within them more memorable, however, gaze is not modulated by lighting differences when viewing images of these windows.
APPROVED
Keywords: Attention; Memory; Light variation; Stained-glass; Perception; Eye-tracking